Dampak Infrastruktur Publik Terhadap Pertumbuhan Ekonomi Di Indonesia - Ikhsanul Farhan; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the impact of public infrastructure on economic growth in Indonesia from 2019 to 2023. The approach used is quantitative with a panel data regression method, utilizing secondary data from the Central Statistics Agency (BPS). The public infrastructure variables analyzed include road length, electricity access, internet access, and educational facilities in 34 provinces. The estimation results show that all public infrastructure variables simultaneously have a significant influence on GRDP per capita. Partially, road length and internet access are proven to have a significant influence on GRDP per capita, indicating that both variables play a role in increasing economic efficiency such as facilitating the distribution of goods and services, and encouraging digital economic activities. Meanwhile, the variables of electricity access and educational facilities (classrooms) do not have a significant effect on GRDP per capita. Although the coefficient of determination in this study is relatively low at 7.76%, this finding confirms that road and internet infrastructure are the driving force of national economic growth. The results of this study highlight the importance of policies in equitable infrastructure development between regions as a foundation for driving long-term economic growth.